STUDY STYLE OF BEST GRADUATES (Case Study of Best Graduates of UIN Antasari Banjarmasin) - Muhammad Hafidz Ilmi (PT Ilmu Inovasi Nusantara, 2023)
One key to a student's success in achieving the title of the best graduate is their learning style. This study aims to explain that learning style greatly influences the outcomes of students' struggles throughout their education at the university. This paper is based on interviews conducted with 7 top graduates from UIN Antasari Banjarmasin, selected through purposive sampling using the homogeneous sampling technique. The theory used in this research is Rita Dunn and Dunn Kanneth's. The research design employed is qualitative case study in descriptive form. The results of this study indicate that the majority of the top graduates entered the university through the test-based admission route, specifically the UM-Mandiri route. The most common reason cited by the top graduates for studying is the demand, which includes task requirements and scholarships. The most effective learning environment is a quiet room away from crowds, and music is effective in enhancing focus or concentration and providing a sense of calm while studying. Studying alone is more effective than studying in groups. The senses used are primarily visual combined with auditory perception. The most effective study time is midnight, and the strategy for dealing with difficulties in understanding lessons or completing tasks is to ask someone who has a better understanding of the material or the assigned task. This study is limited to relatively small data, which allows for further research with a larger data scope.